Effect of hydrogen and 1-Hexanol on combustion, performance and emission characteristics of CRDI CI engine. (1st February 2021) - Santhosh, K.; Kumar, G.N.
Abstract: The effect of hydrogen and 1-Hexanol on engine characteristics was scrutinized in a diesel engine. The experiment was conducted at a variable load of 20% to 80% in step of 20% load and speed of the engine (2000 rpm) was constant throughout the experiment. Initially, the effect of injection time (9°BTDC, 12°BTDC and 15°BTDC) on engine characteristics were studied with 30% 1-Hexanol as fuel and compared with diesel fuel operation. 1-Hexanol showed excellent performance and emission characteristics at advanced injection time compared to standard and retard injection time. Then 10LPM of hydrogen was used in a dual fuel mode with 30% of 1-Hexanol at 15°BTDC. At 80% load, the hydrogen enrichment showed 6.77% higher cylinder pressure and 1.50% lower heat release rate compared to neat diesel. The Hydrogen enrichment improves the thermal efficiency by 5% at 80% load compared to neat diesel and also reduces the nitrogen oxide by 6.66% and hydrocarbon emission by 10% compared to neat diesel. From the experiment, it was noted that 1-Hexanol performance well at advanced injection time and further increment in the performance was made with hydrogen. It is concluded that 1-Hexanol and hydrogen will be a sustainable renewable energy source.